2017
DOI: 10.1007/s40268-017-0194-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Switching from Innovator Infliximab to Biosimilar CT-P13 in Inflammatory Rheumatic Diseases: A Real-World Case Study

Abstract: ObjectiveCT-P13 is a biosimilar with comparable pharmacokinetics, efficacy and safety to its reference product (RP), infliximab. Studies have shown that switching from RP to CT-P13 does not reduce the effectiveness or safety of treatment.MethodsIn this retrospective real-world study, patients with inflammatory diseases treated with RP were switched to CT-P13 (n = 7) or continued on RP (n = 6). Clinical outcomes were compared between groups after four treatment cycles.ResultsCT-P13 demonstrated comparable effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In a small, controlled, single‐centre retrospective, observational study of patients with RA, PsA, and AS, safety and efficacy were compared in those that switched from reference infliximab to CT‐P13 (n = 7) to those that maintained treatment with reference infliximab (n = 6) . Switching did not appear to be related to changes in safety or efficacy in these patients.…”
Section: Resultsmentioning
confidence: 99%
“…In a small, controlled, single‐centre retrospective, observational study of patients with RA, PsA, and AS, safety and efficacy were compared in those that switched from reference infliximab to CT‐P13 (n = 7) to those that maintained treatment with reference infliximab (n = 6) . Switching did not appear to be related to changes in safety or efficacy in these patients.…”
Section: Resultsmentioning
confidence: 99%
“…Six (54.5%) of the 11 patients in this cohort who discontinued biosimilar infliximab did so for subjective reasons without evidence of increased disease activity. Smaller ‘real-world’ observational studies also have confirmed comparable efficacy and safety of transitioning from bio-originator infliximab to biosimilar infliximab CT-P13 to that of continuing treatment with bio-originator infliximab 15…”
mentioning
confidence: 89%
“…Authors found that patients with previous IFX treatment with a duration of >5 years had longer CT-P13 retention. Smaller 'real-world' observational studies also confirmed comparable efficacy and safety of transitioning from originator to biosimilar IFX CT-P13 to that of continuing treatment with biooriginator IFX [71,72].…”
Section: Infliximabmentioning
confidence: 76%